Faktor – Faktor Yang Mempengaruhi Nasabah Dalam Menggunakan Layanan Digital Banking (Deposito Mobile BSI) Dengan Menggunakan Model Unifief Theory Of Acceptance And Use Of Technology (UTAUT): Pada Bank Syariah Indonesia (BSI) KCP Kampung Pajak Labuhan Batu Utara - Ridayanti Ridayanti; Marliyah Marliyah; Juliana Nasution (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This research aims to determine the influence of performance expectancy, effort expectancy, social influence, facilitating conditions on the use of Bank BSI KCP Kampung Tax Labuhan Batu Utara customers in using digital banking services. (BSI mobile deposits). This type of research is quantitative. The data used in this research is primary data obtained through questionnaires with variable instruments using a Likert scale which were distributed to respondents totaling approximately 100 people. The data analysis technique used is a data analysis test consisting of validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, and also using multiple linear analysis, which consists of F test, T test, and test the coefficient of determination (R²) using the SPSS version 22 data processing application. The results of this study show that performance expectancy has no effect, effort expectancy has a significant positive effect, social influence has a significant positive effect, and condition Facilitating conditions do not have a positive effect on Bank BSI KCP Kampung Tax Labuhan Batu Utara customers in using digital banking services (BSI Mobile Deposits).